1992
DOI: 10.1063/1.1143693
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic detuning limit on energy in electron cyclotron resonance x-ray source

Abstract: In this paper, a detailed theoretical analysis of electron acceleration in a TE111 cylindrical resonant cavity used as a cyclotron resonance accelerator is presented. The relativistic detuning limit on energy is found to depend critically on the externally applied dc magnetic field. The optimum value of the magnetic field, for a given operating frequency, electric field, and the cavity dimensions, is calculated. The cavity dimensions are optimized to get maximum peak-to-peak electric field so that higher elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…This will restrict the maximum attainable energy by the electrons. In our earlier work, 26 the relativistic effect was included and from the computational results it was found that the relativistic detuning limit on energy depends critically on the externally applied dc magnetic field. To enhance the maximum attainable electron energy, the cavity dimension can be optimized so that higher E 0 value can be achieved for the same quality factor (Q) of the cavity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This will restrict the maximum attainable energy by the electrons. In our earlier work, 26 the relativistic effect was included and from the computational results it was found that the relativistic detuning limit on energy depends critically on the externally applied dc magnetic field. To enhance the maximum attainable electron energy, the cavity dimension can be optimized so that higher E 0 value can be achieved for the same quality factor (Q) of the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the ECR technique has been used for the production of x-rays. [22][23][24][25][26][27] The microwave source ͑frequency and power͒ used in ECR plasma x-ray source is similar to that of microwave ion source/plasma deposition systems. It is to be noted that the magnetic field configuration is different in ECR x-ray source compared to other ECR plasma devices and also, here the plasma is produced in a cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron acceleration in TE 111 cylindrical cavity is studied using single-particle motion. 11,12,16 The relativistic detuning limit on the final energy of electron is studied as a function of external magnetic field. The present source strength has to be enhanced for reducing the exposure time for imaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] In recent years, x-ray source has been made based on ECR technique and the source is called ECR x-ray source. [11][12][13][14][15][16][17][18][19][20] In ECR x-ray source, electrons are accelerated continuously by matching the cyclotron frequency of the electrons to the microwave frequency ͑2.45 GHz͒. After gaining sufficient energy, these electrons collide with the target/cavity wall and produce bremsstrahlung x rays.…”
Section: Introductionmentioning
confidence: 99%